Meta-aramid paper and preparation method thereof
By preparing nanofiber dispersion and combining high-speed shearing and multi-stage washing technology, the problems of surface bleaching, hair loss and glue translucency that are prone to occur during use of meta-aramid paper is solved, and the meta-aramid paper with high binding force and high uniformity is achieved, which improves its mechanical and insulating properties.
Patent Information
- Application Number
- CN202411919352.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing meta-abramid paper is prone to surface bleaching, hair loss, layering or foaming during use, and is prone to glue translucent when preparing honeycomb materials, affecting performance and cost.
By preparing nanofiber dispersion, the para-aramid chopped fibers and potassium hydroxide were added to dimethyl sulfoxide, stirred and dispersed, mixed with the meta-aramid chopped fibers and precipitant, high-speed shearing and multi-stage water washing, to prepare meta-aramid paper with high binding force and high uniformity.
It improves the uniformity, bonding and insulation properties of meta-aramid paper, reduces the risks of layering, lint and glue translucating, and improves the density and mechanical properties of the paper.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to meta-aramid paper and a preparation method thereof, belonging to the technical field of synthetic fiber paper manufacturing. Background Art
[0002] Meta-aramid paper is made of meta-aramid chopped fibers and meta-aramid fibrils as raw materials through wet papermaking and hot pressing. In meta-aramid paper, chopped fibers are used as skeleton materials and are evenly dispersed in the paper, which determines the physical strength and mechanical properties of the paper; meta-aramid fibrils are used as filling and bonding materials. They are softened by heat during the hot pressing process, and the overall mechanical structure of the paper is formed by bonding the short fibers and their own bonding, giving the paper overall strength and performance. Meta-aramid paper has excellent mechanical properties, dielectric properties, chemical stability and flexible processability, and is widely used in high temperature resistant insulation materials. After being impregnated with glue, it can be made into high-strength and lightweight honeycomb structure materials, which are widely used in aerospace, national defense, electronic communications and other fields.
[0003] However, when the short fibers inside the meta-aramid paper are subjected to friction during use, the surface will be fuzzed and linted. When the thick paper is subjected to alternating loads, it is easy to delaminate or bubble. The low surface strength and interlayer bonding strength limit the application of meta-aramid paper in high-end fields such as aerospace, rail transportation, and national defense. At the same time, when meta-aramid paper is used to prepare honeycomb materials, glue penetration occasionally occurs, which increases the cost of downstream customers.
[0004] In addition, the meta-aramid chopped fibers are prone to flocculation during the dispersion process, which greatly affects the uniformity of the meta-aramid during the papermaking process, and further affects the mechanical properties and insulation properties of the meta-aramid paper.
[0005] In order to improve the bonding strength of aramid fibers, a high-temperature hot-pressing composite molding is used in Chinese patent application CN110886145A to improve the bonding force between fibers. However, aramid fibers are severely plasticized at high temperatures, resulting in a decrease in the tearing performance of aramid paper, and poor bonding and easy delamination of thick paper. In Chinese patent application CN113969427A, a kind of aramid micro-nano fiber with a mesh structure is prepared for preparing aramid paper to improve its internal bonding strength. Although the tensile strength and dielectric strength of aramid paper are improved, the internal bonding strength of aramid paper is not high, and the overall performance still needs to be further improved. In Chinese patent application CN106531374A, flame-retardant insulating composite materials are prepared by stacking aramid paper and polyimide film, etc., which can improve the high temperature resistance and flame retardant properties of composite materials and apply them to transformers of various frequencies. However, these methods introduce powders or film materials of different materials into aramid paper, and the interface effect of different materials causes the interface bonding force of the two materials to be weak, which is easy to delaminate and foam during long-term use.
[0006] In order to improve the uniformity of meta-aramid paper, the prior art usually adopts the method of adding dispersants to improve the dispersibility of aramid chopped fibers. Although there is a certain improvement effect, the method of dispersing fibers with dispersants is expensive, and the addition of dispersants during the preparation process complicates the sewage treatment procedure. In addition, the presence of dispersants affects the temperature resistance and insulation performance of paper.
[0007] Therefore, it is of great value to develop a meta-aramid paper with high bonding strength and high uniformity. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a meta-aramid paper and a preparation method thereof. The meta-aramid paper has higher uniformity, bonding strength and insulation performance, and reduces the risk of delamination and hair loss of the meta-aramid paper during use; at the same time, the density of the meta-aramid paper is increased, the porosity of the meta-aramid paper is reduced, and the risk of glue penetration during the preparation of honeycombs using the meta-aramid paper is greatly reduced.
[0009] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing meta-aramid paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding meta-aramid chopped fibers into the nanofiber dispersion to disperse and mix evenly to obtain the meta-aramid chopped fibers dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the meta-aramid fibrids are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid fibrids; S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid precipitated fibers are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper.
[0010] Furthermore, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
[0011] Furthermore, in step S1, the weight ratio of the para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
[0012] Furthermore, in step S2, when preparing the meta-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 0.05% to 1%.
[0013] Furthermore, in step S2, when preparing the meta-aramid fiber, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
[0014] Furthermore, in step S2, when preparing the meta-aramid fibrid, the high-speed shearing speed is 3500 to 6000 rpm, and the high-speed shearing time is 40 to 90 s.
[0015] Furthermore, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
[0016] Furthermore, the weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is (8-2):(2-8), and the total weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is 10 parts.
[0017] Furthermore, in step S3, the hot pressing conditions are: temperature 180-210° C., vehicle speed 5-18 m / min, and pressure 100-280 N / mm.
[0018] The invention also discloses a meta-aramid paper, and the meta-aramid paper is prepared according to the preparation method of the invention.
[0019] The beneficial effects of the present invention are: 1. The nanofiber dispersion is an anionic system, which is very stable and has a certain viscosity. The system can disperse the meta-aramid chopped fibers and maintain a certain steady state. Without the addition of a dispersant, the meta-aramid chopped fibers can be well dispersed and not easily flocculated. This makes the meta-aramid paper have higher uniformity, better mechanical properties and insulation properties.
[0020] 2. During the precipitation of the nanofiber dispersion in water, para-aramid nanofibers are attached to the surface of the meta-aramid chopped fibers, making the smooth surface of the meta-aramid chopped fibers rough. Therefore, the interfacial bonding strength between the meta-aramid chopped fibers and the meta-aramid chopped fibers, and between the meta-aramid chopped fibers and the meta-aramid precipitated fibers is enhanced, and the inter-fiber bonding force is greater, so that the stress is better transferred and the bonding force of the aramid paper is improved. Moreover, the roughness is not obtained by sacrificing the original performance of the meta-aramid fibers. At the same time, the method can significantly reduce the porosity of the meta-aramid paper, thereby improving the insulation performance of the meta-aramid paper, and obtaining the meta-aramid paper with good mechanical properties. The meta-aramid precipitated surface prepared by the present invention has more tiny wrinkles, which can be more strongly bonded to other fibers and also improve the bonding force of the aramid paper.
[0021] 3. The introduction of para-aramid nanofibers during the preparation of meta-aramid precipitation reduces the crystallinity of meta-aramid precipitation fibers, making them easier to melt during hot pressing, and increasing the bonding strength between fibers, reducing the risk of delamination, fuzzing, and shedding of meta-aramid paper during use. At the same time, it also increases the density of meta-aramid paper, reduces the porosity of meta-aramid paper, and greatly reduces the risk of glue penetration during the preparation of honeycombs using meta-aramid paper.
[0022] 4. Compared with conventional meta-aramid fiber, the low crystallinity meta-aramid fiber of the present invention can achieve good melting and bonding at a relatively low hot pressing temperature, and can significantly reduce production energy consumption while maintaining good mechanical properties of aramid paper. The preparation process of the present invention is simple, energy consumption is low, and it is easy to control. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0025] A method for preparing meta-aramid paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers and potassium hydroxide are added to dimethyl sulfoxide, followed by water and mechanical stirring to obtain a stable nanofiber dispersion; S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding meta-aramid chopped fibers into the nanofiber dispersion to disperse them, and stirring them evenly after a certain period of time to obtain the meta-aramid chopped fibers dispersion; The meta-aramid polymer solution, nanofiber dispersion and precipitating agent are continuously and stably added into a precipitation device, and high-speed shearing is performed to obtain precipitated fibrils, which are then discharged into a water washing tank for further cooling and forming. The cooled and formed precipitated fibrils containing N,N-dimethylacetamide solvent are subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, thereby obtaining meta-aramid fibrils with lower crystallinity. S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid precipitated fibers are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper.
[0026] Specifically, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
[0027] Specifically, in step S1, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
[0028] Specifically, in step S2, when preparing the meta-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 0.05% to 1%.
[0029] Specifically, in step S2, when preparing the meta-aramid fibrid, the meta-aramid polymer solution has a temperature of 35-50° C., a solid content of 8%-15%, and a viscosity of 100-450 Po at 25° C.
[0030] When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
[0031] Specifically, in step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.
[0032] Specifically, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
[0033] More specifically, the storage temperature of the precipitating agent is 4-20°C.
[0034] Specifically, in step S3, the weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is (8-2):(2-8), and the total weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is 10 parts.
[0035] Specifically, in step S3, the hot pressing conditions are: temperature 180-210° C., vehicle speed 5-18 m / min, and pressure 100-280 N / mm.
[0036] More specifically, the para-aramid chopped fibers and meta-aramid chopped fibers used in the embodiments of the present invention are produced by Taihe New Materials Group Co., Ltd., with a length of 4 to 8 mm and a fineness of 1.5 dtex to 2.0 dtex; the solvents in the meta-aramid polymer solution used in the embodiments of the present invention are all N,N-dimethylacetamide.
[0037] A meta-aramid paper is prepared according to the preparation method of the present invention.
[0038] Example 1 Preparation of a meta-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (1.5 dtex, 5 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 12 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fibers, dimethyl sulfoxide, water and potassium hydroxide is 1.5:95:0.06:2.5; and the storage temperature condition of the nanofiber dispersion is 20°C.
[0039] S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of meta-aramid chopped fiber dispersion: The meta-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 12 minutes, the meta-aramid chopped fibers are uniformly stirred to obtain the meta-aramid chopped fibers dispersion; wherein the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fibers dispersion is 0.8%.
[0040] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 15:10:90; The temperature of the meta-aramid polymerization liquid is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C.
[0041] In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0042] S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid fibrils are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper; The weight ratio of the meta-aramid chopped fibers to the meta-aramid fibrils in the meta-aramid chopped fibers dispersion is 4:6. The hot pressing conditions were: temperature 190 °C, speed 15 m / min, and pressure 180 N / mm.
[0043] Example 2 Preparation of a meta-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (2 dtex, 5 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 24 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 0.05:85:0.02:0.15; and the storage temperature condition of the nanofiber dispersion is 15°C.
[0044] S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of meta-aramid chopped fiber dispersion: Add meta-aramid chopped fibers (2 dtex, 5 mm) into the nanofiber dispersion for debonding. After debonding for 15 minutes, stir evenly to obtain the meta-aramid chopped fiber dispersion. The mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 1%.
[0045] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 6000 rpm for 40 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 20:12:100; The temperature of the meta-aramid polymerization liquid is 40°C, the solid content is 8%, and the viscosity is 100Po at 25°C.
[0046] In terms of weight, the precipitating agent is composed of 5 parts of lithium chloride, 45 parts of water, and 50 parts of N,N-dimethylacetamide.
[0047] S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid fibrils are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper; The weight ratio of the meta-aramid chopped fibers to the meta-aramid precipitated fibers in the meta-aramid chopped fibers dispersion is 2:8. The hot pressing conditions were: temperature 180 °C, speed 5 m / min, and pressure 100 N / mm.
[0048] Example 3 Preparation of a meta-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (1.7 dtex, 6 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 4 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid chopped fibers, dimethyl sulfoxide, water and potassium hydroxide is 3:100:0.08:4; and the storage temperature condition of the nanofiber dispersion is 25°C.
[0049] S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of meta-aramid chopped fiber dispersion: Add meta-aramid chopped fibers (1.5 dtex, 6 mm) into the nanofiber dispersion for decomposition, and after decomposition for 5 minutes, stir evenly to obtain the meta-aramid chopped fiber dispersion; wherein the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 0.05%.
[0050] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 3500 rpm for 90 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 5:5:80; The temperature of the meta-aramid polymerization liquid is 50°C, the solid content is 15%, and the viscosity is 450Po at 25°C.
[0051] In terms of weight, the precipitating agent is composed of: 18 parts of magnesium chloride, 42 parts of water, and 40 parts of N,N-dimethylacetamide.
[0052] S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid fibrils are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper; The weight ratio of the meta-aramid chopped fibers to the meta-aramid fibrils in the meta-aramid chopped fibers dispersion is 8:2. The hot pressing conditions were: temperature 210 °C, vehicle speed 18 m / min, and pressure 280 N / mm.
[0053] Example 4 Preparation of a meta-aramid paper: S1. Preparation of nanofiber dispersion: Para-aramid chopped fibers (2 dtex, 6 mm) and potassium hydroxide are added to dimethyl sulfoxide, and then water is added and mechanically stirred for 16 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 1:80:0.01:1; and the storage temperature condition of the nanofiber dispersion is 25°C.
[0054] S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of meta-aramid chopped fiber dispersion: Add meta-aramid chopped fibers (1.5 dtex, 5 mm) into the nanofiber dispersion for debonding. After debonding for 8 minutes, stir evenly to obtain the meta-aramid chopped fiber dispersion. The mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 0.15%.
[0055] (2) Preparation of meta-aramid fiber precipitation: The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 10:10:90; The temperature of the meta-aramid polymerization liquid is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C.
[0056] In terms of weight, the precipitating agent is composed of: 15 parts of calcium chloride, 45 parts of water, and 40 parts of N,N-dimethylacetamide.
[0057] S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid fibrils are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper; The weight ratio of the meta-aramid chopped fibers to the meta-aramid fibrils in the meta-aramid chopped fibers dispersion is 6:4. The hot pressing conditions were: temperature 200 °C, speed 18 m / min, and pressure 160 N / mm.
[0058] Comparative Example 1 The meta-aramid paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was increased. In this comparative example 1, the storage temperature of the nanofiber dispersion was 35°C.
[0059] Comparative Example 2 The meta-aramid paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was lowered. In this comparative example 2, the storage temperature of the nanofiber dispersion was 5°C.
[0060] Comparative Example 3 The same method as in Example 1 is adopted to prepare meta-aramid paper, except that in step S2, when preparing meta-aramid fibrillation, the dosage ratio of nanofiber dispersion is increased. In this comparative example 3, the weight ratio of nanofiber dispersion, precipitating agent and meta-aramid polymerization liquid is 25:10:90.
[0061] Comparative Example 4 The same method as in Example 1 is adopted to prepare meta-aramid paper, except that in step S2, when preparing meta-aramid fibrillation, the dosage ratio of nanofiber dispersion is reduced. In this comparative example 4, the weight ratio of nanofiber dispersion, precipitating agent and meta-aramid polymerization liquid is 1:10:90.
[0062] Comparative Example 5 The meta-aramid paper was prepared by the same method as in Example 1, except that in step S2, when preparing the meta-aramid fibrid, the shear rate was increased. In this comparative example 5, the shear rate of step S2 was 8000 rpm.
[0063] Comparative Example 6 The meta-aramid paper was prepared by the same method as in Example 1, except that in step S2, when preparing the meta-aramid fibrid, the shear rate was reduced. In this comparative example 6, the shear rate of step S2 was 2000 rpm.
[0064] Comparative Example 7 The conventional method is to coat the nanofiber dispersion on the surface of aramid paper. The specific preparation process is as follows: S1. Preparation of nanofiber dispersion: The nanofiber dispersion was prepared by the same method as in Example 1; S2. Preparation of meta-aramid paper: The meta-aramid short fibers and the meta-aramid fibrils are debonded, stirred, wet-formed, pressed, and dried to obtain the meta-aramid base paper; wherein the weight ratio of the meta-aramid short fibers to the meta-aramid fibrils is 4:6; S3. Coating of nanofiber dispersion: One side of the meta-aramid paper prepared in step S2 is uniformly coated with the nanofiber dispersion prepared in step S1, and then washed and dried, and then the above steps are repeated on the other side of the meta-aramid paper to control the total coating amount of nanofibers on the meta-aramid paper to be 2 g / m 2 Finally, the meta-aramid paper coated with nanofibers on both sides was hot pressed to obtain the final product. The hot pressing conditions were: temperature 190°C, speed 15m / min, and pressure 180N / mm.
[0065] Comparative Example 8 The meta-aramid paper was prepared by the same method as in Example 1, except that the meta-aramid chopped fiber dispersion and the meta-aramid fibrid were prepared by a conventional method. That is, the nanofiber dispersion was not used when preparing the meta-aramid chopped fiber dispersion in Comparative Example 8, and the nanofiber liquid was not added in the process of preparing the meta-aramid fibrid.
[0066] The specific preparation process of the meta-aramid chopped fiber dispersion in Comparative Example 8 is as follows: The meta-aramid chopped fibers are added into a proper amount of water for decomposition, and after decomposition for 12 minutes, the meta-aramid chopped fibers are uniformly stirred to obtain the meta-aramid chopped fibers dispersion; wherein the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fibers dispersion is 0.8%.
[0067] The specific preparation process of the meta-aramid fiber dispersion in Comparative Example 8 is as follows: The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; Wherein, the weight ratio of the precipitating agent to the meta-aramid polymer solution is 10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity at 25°C is 300Po; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0068] Then, the meta-aramid chopped fiber dispersion and meta-aramid fibrid prepared in this comparative example 8 were deflaked and stirred, and then wet-formed, pressed, dried, and hot-pressed to obtain meta-aramid paper in the same manner as in Example 1.
[0069] Comparative Example 9 The meta-aramid paper was prepared by the same method as in Example 1, except that: the meta-aramid chopped fiber dispersion was prepared by a conventional method, that is, no nanofiber dispersion was used when preparing the meta-aramid chopped fiber dispersion in this comparative example 9. The specific preparation process of the meta-aramid chopped fiber dispersion in this comparative example 9 is as follows: The meta-aramid chopped fibers are added into a proper amount of water for decomposition, and after decomposition for 12 minutes, the meta-aramid chopped fibers are uniformly stirred to obtain the meta-aramid chopped fibers dispersion; wherein the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fibers dispersion is 0.8%.
[0070] Comparative Example 10 The meta-aramid paper was prepared by the same method as in Example 1, except that the meta-aramid fibrid was prepared by a conventional method, that is, no nanofiber dispersion was used in the preparation of the meta-aramid fibrid in this comparative example 10. The specific preparation process of the meta-aramid fibrid in this comparative example 10 is as follows: The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; Wherein, the weight ratio of the precipitating agent to the meta-aramid polymer solution is 10:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0071] The aramid papers prepared in the above examples and comparative examples were subjected to performance tests, and the test methods involved are specifically as follows.
[0072] The quantitative test method refers to the standard GB / T 451.2; The thickness test method refers to GB / T 451.3; The reference standard for tensile strength and elongation test methods is GB / T 12914; The tear strength test method refers to GB / T 455; The dielectric strength test method refers to GB / T 1408.1; The surface strength test method refers to the standard GB / T 22837; The internal bonding strength test method refers to the standard GB / T 26203; The uniformity index is measured by the testing instrument Micro-Scanner; The porosity is measured by a mercury intrusion tester; The specific test results are shown in Tables 1 and 2 below.
[0073] Table 1 Mechanical properties test data of meta-aramid paper
[0074] Table 2 Other performance test data of meta-aramid paper
[0075] It can be seen from the above table data that the meta-aramid paper prepared by the preparation method of the present invention in Examples 1-4 has good uniformity, low porosity, and excellent mechanical properties and insulation properties. And the meta-aramid paper prepared by the preparation method of the present invention in Examples 1-4 has high surface strength and internal bonding strength, which can largely avoid stratification and fuzzing, and improve user satisfaction. At the same time, the reduction in porosity also reduces the risk of glue penetration during the preparation of honeycombs from meta-aramid paper. The intermediate aramid short fibers in Examples 1-4 of the present invention are well dispersed in the nano-dispersion liquid, which significantly improves the overall performance of the meta-aramid paper. At the same time, the aramid nanofibers adhered to the surface of the meta-aramid short fibers act as a binder, which not only fills the pores of the meta-aramid paper, but also strengthens the interaction with other fibers. In addition, the introduction of nanofiber dispersion in the preparation process of meta-aramid precipitated fibers moderately reduces its crystallinity, meeting the balance between energy saving and excellent performance in the processing process. Compared with conventional meta-aramid fiber precipitates, the meta-aramid fiber precipitates prepared by the present invention have more tiny wrinkles on the surface, and can have stronger bonding force with other fibers. At the same time, strong hydrogen bonding force can be formed between the aramid nanofibers and the meta-aramid short chopped fibers or the meta-aramid fiber precipitates. Under multiple effects, the meta-aramid paper in the present invention has excellent overall performance.
[0076] From the data comparison of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that if the storage temperature of the nano-dispersion liquid is increased or decreased, the mechanical properties, compressive strength, surface strength, internal bonding strength, uniformity and other indicators of the meta-aramid paper will be significantly reduced. This is because the nano-dispersion liquid is at a suitable temperature, the aramid short fibers will be dispersed more evenly, the size of the prepared meta-aramid fibrils will be more uniform, and the appropriate crystallinity and microscopic morphology (i.e., the surface has more tiny wrinkles) will be maintained. Therefore, the overall performance of the aramid paper finally prepared is significantly improved.
[0077] From the data comparison of Comparative Examples 3, 4 and Example 1, it can be seen that if the proportion of nanofibers is increased or decreased, the overall performance of meta-aramid paper will also be significantly reduced. This is because by selecting a suitable nanofiber ratio, the meta-aramid fibrils prepared will have a more uniform size and maintain a suitable crystallinity and microscopic morphology, and the mechanical properties of the prepared meta-aramid paper will be better and the compressive strength will be higher. At the same time, by selecting a suitable nanofiber ratio, the dispersed state of the aramid chopped fibers is more conducive to achieving the optimal state and giving the aramid paper as a whole good overall performance.
[0078] From the data comparison of comparative example 5, comparative example 6 and embodiment 1, it can be seen that maintaining a suitable shear rate can improve the overall performance of meta-aramid paper. When the shear rate is too high, the length of meta-aramid fibrid will be shortened, and the film characteristics of meta-aramid fibrid will also be reduced, which will cause the contact area between meta-aramid fibrid and aramid short-cut fibers to be reduced, resulting in the reduction of mechanical properties, compressive strength and other properties of paper. When the shear rate is too low, the shear force received by the aramid droplets is not enough, and the aramid droplets dispersed in the precipitant are relatively large, and it is impossible to fully stretch into a film state, thereby causing the overall performance of the meta-aramid paper to decrease. In addition, maintaining a certain shear rate is crucial for the crystallinity of meta-aramid fibrid. The shear rate is too high, and the aramid droplets are under the high-speed shearing action, and the fiber is easy to present a film state, and the crystalline structure is destroyed, resulting in a low crystallinity, thereby reducing the fiber strength, and further reducing the mechanical properties of the aramid paper. On the contrary, if the shear rate is too low, the crystallinity of meta-aramid fibrid is too high, the polymer chain segments are over-aggregated, the gaps are reduced, the flexibility of the molecular chain is reduced, and the mechanical properties of the paper are reduced. The present invention controls the conditions so that the crystallinity of the prepared meta-aramid fibrid is moderately reduced compared with the traditional meta-aramid fibrid, which can not only save energy consumption in the hot pressing process, but also significantly improve the overall performance of the meta-aramid paper.
[0079] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that compared with the method of coating the nanofibers on the surface of the aramid paper, the meta-aramid paper in the present invention has better overall performance.
[0080] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that compared with the conventional preparation method of meta-aramid paper, the meta-aramid paper prepared by the present invention has significantly improved mechanical properties, compressive strength, and internal and surface strength of paper, avoiding phenomena such as fuzzing and delamination during the use of paper.
[0081] From the comparison of the data of Comparative Examples 9 and 10 and Example 1, it can be seen that the aramid paper prepared by using both the meta-aramid fibrid and the meta-aramid chopped fiber dispersion of the present invention has better overall performance.
[0082] In summary, the meta-aramid paper of the present invention has higher tensile strength, uniformity, tightness and insulation performance, and also has better internal bonding force and surface strength, thereby avoiding the occurrence of delamination and fuzzing during use and glue penetration during honeycomb preparation.
[0083] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing meta-aramid paper, characterized in that: The preparation method is: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of meta-aramid chopped fiber dispersion and meta-aramid fiber precipitation: Adding meta-aramid chopped fibers into the nanofiber dispersion to disperse and mix evenly to obtain the meta-aramid chopped fibers dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the meta-aramid fibrids are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid fibrids; S3. Preparation of meta-aramid paper: The meta-aramid short fiber dispersion and the meta-aramid precipitated fibers are subjected to delamination, stirring, wet forming, pressing, drying and hot pressing to obtain the meta-aramid paper.
2. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
3. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S1, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
4. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid chopped fiber dispersion, the deflaking time is 5 to 15 minutes; and the mass concentration of the meta-aramid chopped fibers in the meta-aramid chopped fiber dispersion is 0.05% to 1%.
5. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
6. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.
7. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
8. The method for preparing meta-aramid paper according to claim 1, characterized in that: The weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is (8-2):(2-8), and the total weight ratio of the meta-aramid chopped fibers and the meta-aramid fibrids in the meta-aramid chopped fiber dispersion is 10 parts.
9. The method for preparing meta-aramid paper according to claim 1, characterized in that: In step S3, the hot pressing conditions are: temperature 180-210° C., vehicle speed 5-18 m / min, and pressure 100-280 N / mm.
10. A meta-aramid paper, characterized in that: The meta-aramid paper is prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Flame-retardant insulated composite material and preparation technology thereof
CN106531374A
Hot press molding method of meta-aramid thick paper
CN110886145A
Aramid fiber micro-nano fiber with net-shaped structure as well as preparation method and application of aramid fiber micro-nano fiber
CN113969427A
Aramid fiber modification method
CN113389080A
Para-aramid nanofiber reinforced modified meta-aramid fiber and preparation method thereof
CN118029001A
Cited By
Aramid fiber composite non-woven fabric and preparation method and application thereof
CN121719124A